Influence Rotasi of Crop Rotation Pattrens on Ralstonia solanacearum Population In The Soil and on The Potato crop in The Subsequent Season - Nikardi Gunadi; E. Chujoy; M. Kusmana; O. S. Gunawan; Rofik Sinung Basuki (Jurnal Ilmu Pertanian, 2006)
-